Pathogenetic Therapy of Patients with Recurrent Genital Herpes - L. L. Logvina; D. N. Bayram; Z. A. Kambachokova; F. V. Shavaeva; Z. S. Krymshokalova; M. M. Sarbasheva; M. Kh. Kardanova; K. O. Iosipchuk (Антибиотики и Химиотерапия)
Evaluation of the effectiveness of aminophthalhydroside in the complex treatment of patients with recurrent genital herpes was carried out. The efficacy of the drug was assessed by clinical, biochemical, and immunological criteria. The inclusion of aminophthalhydrazide in the complex therapy of patients with recurrent herpesvirus infection led to an earlier relief of clinical manifestations of the disease, an increase in the relapse period, a decrease in lipid peroxidation products in the blood plasma, an increase in the content of antioxidant defense components, and correction of immunological disorders.